Religion, values and ethics for 11-14 years - Parry, Lesley; Hayes, Jan (Curriculum for Wales, 2022)
Confidently deliver Religion, Values and Ethics and encourage students to understand and appreciate diverse worldviews, both in Wales and the wider world. This book supports the new Curriculum for Wales for 11-14 years, helping students to continually develop their knowledge and skills as they become informed, self-aware and responsible citizens. - Easily design your own curriculum: pick-and-choose from topics that cover the major world faiths and non-religious belief groups, as well as the values and ethical content outlined in the Humanities AoLE - Understand religious and non-religious worldviews and their historical impact: examine the influence of institutional and personal religious and non-religious worldviews on Wales and the wider world throughout history - Bring the content to life in your classroom: explore the beliefs and practices of people living today in Wales and the wider world through real-life accounts and case studies - Encourage critical thinking: each lesson tackles a 'big question' for students to consider, as well as activities designed to allow them to formulate and express their own perspectives and a range of sources to engage them with ethical and moral issues - Develop students' sense of self and their understanding of societal challenges: explore key concepts in the context of different religious and ethical worldviews, including cynefin, identity, relationships, community, equality, sustainability, freedom, good and evil, and more.